PENGEMBANGAN KELAS VIRTUAL BERBASIS FLIPPED LEARNING UNTUK MENINGKATKAN PENGUASAAN KONSEP SAINS SISWA SEKOLAH DASAR - Hidayat, Hidayat (LPMP Provinsi DKI Jakarta, 2024)
The low ability of students in learning activities influences the level of mastery of students' science concepts in class. This research aims to develop a virtual class with a flipped learning model to improve mastery of science concepts for class VI students at SDN Pulau Kelapa 02 Pagi. The data collection technique in development research is to obtain validation from experts, namely media, language, and material experts, through interviews, observations, and student learning outcomes tests. Data analysis is carried out by presenting data and drawing conclusions and quantitative data is carried out by converting student assessment results to the completion of minimum criteria. The research results show that the validation results for media experts are 98%, language experts are 92% and material experts are 98% with an average of 96% and these results can be categorized as very valid. The practical level of developing this virtual class reached 96% and was categorized as very practical when implemented in elementary schools. Mastering the concepts of science material also seems to have a positive impact, namely the student completion rate reached 88.8%. It can be concluded that the development of virtual classes with a flipped learning strategy has an impact on increasing students' mastery of science concepts in class VI as well as fostering interest, learning activities and problem solving in students.